CRITICAL DISCOURSE ANALYSIS OF REPRESENTATION OF WOMAN EMPOWERMENT IN THE “NEW WOMAN” SONG’S LYRICS BY LALISA FEAT ROSALIA - THE ENGLISH VERSION - Afiyanti, Sylvi Nur; Heribertus Binawan (Journal of Innovation Research and Knowledge, 2025)
This research uses Norman Fairclough's Critical Discourse Analysis (CDA) paradigm to analyze how Lisa and Rosalía's song "New Woman" depicts female empowerment. It focuses on textual analysis, discursive practices, and social practices. Through the use of first-person pronouns and a strong declarative-imperative sentence structure, the textual analysis demonstrates how agency and self-confidence are constructed. Strategic word choices like "bangin'," "root," "bloom," "aura," "swerve," and "liberate" together portray a potent path of personal emancipation, boundary-breaking, and self-transformation. The visual narrative in the music video, Lisa's dual role as co-writer and her collaboration with Rosalía, and the song's empowering message and global reach are all strengthened at the discursive practice level. Furthermore, "New Woman" speaks to the universal struggle of women against patriarchal norms, beauty standards, and social constraints in addition to reflecting Lisa's own experience of overcoming discrimination and pressures in the music industry. The study's conclusion reaffirms the transformative power of popular music in forming modern social narratives and affirms that "New Woman" is more than just a piece of music; it is a significant cultural and political statement that encourages gender equality and challenges stereotypes.